Compton scattering and charge transfer in Er substituted DyAl2. (February 2015) - Ahuja, B.L.; Mohammad, F.M.; Mohammed, S.F.; Sahariya, Jagrati; Mund, H.S.; Heda, N.L.
Abstract: A unique applicability of Compton spectroscopy in probing the electronic states of rare earth aluminides using high energy (662 keV) γ-rays is reported. We have measured first-ever Compton profiles of Dy1- x Er x Al2 ( x =0, 0.2) using 20Ci 137 Cs Compton spectrometer. The charge reorganization in Dy1 −x Er x Al2 ( x =0, 0.2), on the formation of compound, has been discussed using the valence band Compton profile data. The experimental Compton profile data unambiguously establish charge transfer from Al to Dy (Dy and Er) on formation of x =0.0 (0.2) compound, which is in tune with spin polarized relativistic Korringa–Kohn–Rostoker (SPR-KKR) calculations. A reasonable agreement between SPR-KKR based Compton profiles and the experimental data show applicability of the Green function method in predicting the electronic properties of rare earth compounds. Highlights: Measured first ever Compton profiles (CPs) of DyAl2 and Dy0.8 Er0.2 Al2 compounds. Established CP technique for charge reorganization in ternary rare earth compounds. Calculated charge transfer using density of states and CPs within SPR-KKR method. Presented a trend setting method to analyze CP data in ternary rare earth compounds.